2017
DOI: 10.14744/ejmo.2017.83997
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Arteriovenous Fistula Created for Hemodialysis Access and Treatment Approaches

Abstract: Objectives:Patients with chronic renal failure who are treated with hemodialysis need a patent arteriovenous fistula (AVF). This study was an analysis to determine the best approach to prevent complications and provide treatment. Methods: In this retrospective study, a total of 437 AVF patients' medical records and postoperative epicrisis with 4 years of clinical follow-up were evaluated. The preferred method of anastomosis surgery was the end-to-side technique. Complications were divided into categories of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…The majority of the patients were males with 79%, while females were 21%. This demography is similar to the studies by Fitzgerald et al, 11 Shahnawaz et al, 12 Demiral et al, 13 Korepta et al, 14 and Yoo et al, 15 who all documented in their respective studies that higher percentages of men had AVF access created for haemodialysis. Similarly, the mean ages of 55, 56 and 59 years were reported by Sahasrabudhe et al, 16 Fitzgerald et al, 11 and Yoo et al, 15 respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The majority of the patients were males with 79%, while females were 21%. This demography is similar to the studies by Fitzgerald et al, 11 Shahnawaz et al, 12 Demiral et al, 13 Korepta et al, 14 and Yoo et al, 15 who all documented in their respective studies that higher percentages of men had AVF access created for haemodialysis. Similarly, the mean ages of 55, 56 and 59 years were reported by Sahasrabudhe et al, 16 Fitzgerald et al, 11 and Yoo et al, 15 respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Others were seroma (4,60%), spontaneous thrombosis (4.60%), superficial wound infection (3.45%), steal syndrome (1.15%) and upper limb oedema (1.15%). Previous studies had reported complication rates of 17.7%, 16 22.22%, 21 33.18% 13 and 47% 11 respectively in their studies.…”
Section: Discussionmentioning
confidence: 89%
“…3 another study by Demiral S et.al, DM was found in 43.2% patients and hypertension was found in 13.2% patients. 7 this difference is due to variable disease burden in different parts of the world with DM being the leading cause of ESRD in Indian subcontinenet and Hypertension in the western countries. 3 The preferred site of AVF is radiocephalic followed by brachiocephalic fistula, 7 however in patients with DM and peripheral vascular disease, brachiocephalic fistula is preferred to avoid complications related to vascular access and maintenance of fistula.…”
Section: Discussionmentioning
confidence: 99%
“…7 this difference is due to variable disease burden in different parts of the world with DM being the leading cause of ESRD in Indian subcontinenet and Hypertension in the western countries. 3 The preferred site of AVF is radiocephalic followed by brachiocephalic fistula, 7 however in patients with DM and peripheral vascular disease, brachiocephalic fistula is preferred to avoid complications related to vascular access and maintenance of fistula. 7 As most of the patients in our study were diabetic with deficiency of peripheral venous structures, brachiocephalic fistula was preferably constructed in majority of the patients (56%) to avoid its complicatins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation